Nutritional strategies for endurance cyclists - periodized nutrition, ketogenic diets, and other considerations - Wei, R. J.; Orbeta, L.; Hatamiya, N. S.; Chang, C. J. (Current Sports Medicine Reports, 2023)
Cycling is a growing sport worldwide since the COVID-19 pandemic. With the growing availability and interest in long distance events, professional and amateur cyclists are pushing themselves further and harder than ever before. Training and nutrition should be understood by the sports medicine professional in order to guide counseling toward proper fueling to avoid health consequences. This article reviews macronutrients and micronutrients, periodized training and nutrition, and the relevance of the ketogenic diet for endurance cyclists riding greater than 90 min.